Credit default swaps in a roll-over risk framework - Petersen, Nicholas (Department of Finance and Tax, 2022)
Spreads between swap legs referencing floating cashflows of different tenors have widened significantly since the global financial crisis of 2008. This frequency basis can be explained by the presence of “roll-over risk”. Defining the roll-over risk state variables in an affine form, this dissertation prices a credit default swap using an “affine transform” methodology. This price is then compared to that obtained from a traditional Monte Carlo simulation approach. The former is shown to produce accurate results with greater computational efficiency, providing a useful way to price complex financial instruments when the state variables are defined in an appropriate form.